Pendampingan UMKM Samja Eat and Drink untuk Meningkatkan Brand Awareness melalui Optimalisasi Instagram dalam Program Kreativitas Mahasiswa - Endhita Asmarani Miswanto; Nisa Febrina Maushal; Danang Rusdawindra Samiaji; Johan Hendri Prasetyo (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
This community service initiative aimed to enhance the brand awareness of Samja Eat and Drink, a small business (MSME) in East Jakarta, through structured Instagram management. The business initially faced challenges such as low follower growth, inconsistent content production, and fluctuating customer visits. The assistance program adopted a systematic approach consisting of structured mentoring sessions, digital literacy training, strategic content planning, and collaboration with local influencers. Over four months, the initiative produced notable outcomes, the Instagram account’s reach, a key indicator of brand awareness increased by 1,448%, follower growth rose steadily by 3.9%, and engagement rates remained high, with 69–90% of content views coming from non-followers. These findings demonstrate that a comprehensive and method-based social media mentoring model can significantly improve MSME brand visibility and stimulate meaningful audience interaction. The activity contributes to the growing literature on MSME digital transformation and provides practical implications for small businesses seeking to strengthen competitiveness through enhanced digital literacy and strategic social media capabilities.